Animal welfare and product quality aspects of fish processing: Irodalmi összefoglalás - Varga, Dániel; Szabó, András; Romvári, Róbert; Hancz, Csaba (Animal welfare, Ethology and Housing Systems (AWETH), 2011)
Due to the perimortal stress the biochemical processes change in blood and tissues, e.g. the lactate and the glucose level increases. These changes have an impact on the post mortem processes and modify the quality of the product. In this paper authors give a review on the circumstances meaning stress for the fishes, and how to modify the flesh quality.